An artificial light-harvesting system based on the ESIPT–AIE–FRET triple fluorescence mechanism. Issue 15 (18th March 2022) - Xiao, Tangxin; Bao, Cheng; Zhang, Liangliang; Diao, Kai; Ren, Dongxing; Wei, Chunxiang; Li, Zheng-Yi; Sun, Xiao-Qiang
Abstract : A Schiff-base derived TPE dimer has been designed and synthesized, which could be further prepared as NPs in water with tunable emission and sensing ability controlled by an integration of fluorescence mechanisms including ESIPT, AIE, and FRET. Abstract : It is of great significance to combine different fluorescence mechanisms to accurately regulate the properties of organic fluorescent materials, such as the Stokes shift, emission intensity and photoluminescence color. In this paper, we employ an integration of three fluorescence mechanisms, i.e. aggregation-induced emission (AIE), excited-state intramolecular proton-transfer (ESIPT), and Förster resonance energy transfer (FRET), to fabricate an efficient light-harvesting system (LHS). We firstly designed and synthesized a spirocyclic spacer bridged tetraphenylethylene (TPE) dimer L, in which the spacer and TPE are linked together by Schiff-base groups. The TPE units endow L with AIE behavior, while the Schiff-base groups offer L with ESIPT properties. Subsequently, highly fluorescent nanoparticles (NPs) with large Stokes shift were prepared by a facile reprecipitation strategy from L based on the ESIPT–AIE dual mechanism. By employing L as an energy donor and a dye NDI as an energy acceptor, an efficient artificial LHS with tunable properties could be constructed as dispersed NPs in water solution ( f w = 90%) based on the ESIPT–AIE–FRET triple mechanism. The LHS showed satisfactory energy-transfer efficiency and a high antenna effect. In addition, the fabricated LHS was applied in the selective detection of Cu 2+ ions and exhibited excellent sensing capabilities with a large Stokes shift and red fluorescence quenching responsiveness. The present work will open a new avenue for developing tunable multi-mechanism fluorescent materials and show great potential applications in the fields of sensing, bio-imaging, and light-harvesting devices.